Rock mechanics for construction of the gravimeter vault at the Matjiesfontein Space Geodesy and Earth Observation Observatory - Van Wyk, Peter Ryan (Stellenbosch : Stellenbosch University, 2013)
Thesis (MEng)--Stellenbosch University, 2013.